2003
DOI: 10.1002/bdd.369
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic characterization of a human immunodeficiency virus protease inhibitor, saquinavir, during ethanol intake in rats

Abstract: Throughout therapeutic drug monitoring of human immunodeficiency virus (HIV) protease inhibitors in HIV-infected patients, it was found that plasma concentrations of saquinavir (SQV) were reduced in patients who had a habit of alcohol intake during double protease therapy with SQV and ritonavir (RTV). This study confirmed the pharmacokinetic profiles of SQV during ethanol intake in rats. After oral administration of SQV alone (20 mg/kg) in rats prepared by free access to 15% ethanol solution for 14 days (day 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Nonetheless, this is an important finding in context with the report that alcohol is known to increase the toxicity and reduce the efficacy of HAART in HIV-1-infected individuals [26,28,86-88]. More specifically, the studies from Flexner and colleagues [88] and Shibata and colleagues [89,90] have shown that alcohol can increase the metabolism and decrease the bioavailability of PI and NNRTI, resulting in decreased efficacy. The presence of multiple PI and/or NNRTI in HAART regimen, in which PI also act as CYP3A4 inhibitors, make alcohol–CYP3A4–PI interactions complex.…”
Section: Role Of Cyp3a4 In Alcohol–haart Interaction and Its Implimentioning
confidence: 57%
“…Nonetheless, this is an important finding in context with the report that alcohol is known to increase the toxicity and reduce the efficacy of HAART in HIV-1-infected individuals [26,28,86-88]. More specifically, the studies from Flexner and colleagues [88] and Shibata and colleagues [89,90] have shown that alcohol can increase the metabolism and decrease the bioavailability of PI and NNRTI, resulting in decreased efficacy. The presence of multiple PI and/or NNRTI in HAART regimen, in which PI also act as CYP3A4 inhibitors, make alcohol–CYP3A4–PI interactions complex.…”
Section: Role Of Cyp3a4 In Alcohol–haart Interaction and Its Implimentioning
confidence: 57%
“…The bioavailability of SQV after oral administration alone to rats treated with 15% ethanol solution for 14 d (Day 14 rats) decreased significantly by 51% as compared to non treated (NT) rats. 5) Moreover, total body clearance of SQV after intravenous administration alone to the Day 14 rats increased slightly by 30% as compared to the NT rats. 5) Although most alcoholic beverages contain 0.13 to 0.5% isopentanols that inhibit CYP3A, 6) it has been well known that the greater part of constituent of alcohol beverages, ethanol, induces mainly CYP2E1.…”
mentioning
confidence: 90%
“…5) Moreover, total body clearance of SQV after intravenous administration alone to the Day 14 rats increased slightly by 30% as compared to the NT rats. 5) Although most alcoholic beverages contain 0.13 to 0.5% isopentanols that inhibit CYP3A, 6) it has been well known that the greater part of constituent of alcohol beverages, ethanol, induces mainly CYP2E1. Since SQV is one of PIs to be used for HAART therapy and is mainly metabolized via CYP3A4, 7) a room to clarify the reason that ethanol decreases the bioavailability of SQV after oral administration has been remained.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…After intravenous administration, samples were collected at 8 to 10 h, which was considered to represent the terminal phase, because previous studies have estimated the half-life (t 1/2 ) of SQV to be 1.6 h in rats (Shibata et al, 2003). However, after intraperitoneal and oral administration, profiles showed that the initial protocol sampling times (up to 8 -10 h) had not adequately captured the terminal phase and were therefore modified.…”
Section: Introductionmentioning
confidence: 99%